2019
DOI: 10.1111/jocd.12939
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of imiquimod 5% cream as an anti‐wrinkle treatment: A pilot study

Abstract: Summary Background Imiquimod 5% cream is currently approved to treat several dermatologic conditions including actinic keratoses (AK), superficial basal cell carcinoma (sBCC), and genital warts. However, there are numerous studies published on the alternative off‐label uses of imiquimod cream. Photoaging of facial skin is an important use for topical skin treatments, yet few studies have evaluated the effect of imiquimod cream for this dermatological condition. Methods This was a prospective, noncomparative pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A study conducted by Metcalf et al demonstrated a significant increase in papillary dermal fibroplasia with an associated reduction in solar elastosis and restoration of normal epidermal thickness after IMI cream treatment [ 37 ]. Finally, a prospective non-comparative pilot study demonstrated the anti-aging effect of IMI 5% cream in 72.7% of patients who applied the treatment on the periorbital skin, based on the self-assessed 5-point Likert scale [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Metcalf et al demonstrated a significant increase in papillary dermal fibroplasia with an associated reduction in solar elastosis and restoration of normal epidermal thickness after IMI cream treatment [ 37 ]. Finally, a prospective non-comparative pilot study demonstrated the anti-aging effect of IMI 5% cream in 72.7% of patients who applied the treatment on the periorbital skin, based on the self-assessed 5-point Likert scale [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Imiquimod (IMQ) is a toll-like receptor (TLR) 7 and 8 agonist used topically to treat external genital and perianal warts caused by human papilloma virus, actinic keratosis and superficial basal cell carcinomas and potential to treat many other skin disorders [18][19][20][21][22][23][24][25][26]. Through activation of its receptors, IMQ application, even on a short-term basis, triggers inflammatory skin reactions that closely resemble those seen in psoriasis [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Imiquimod (IMQ) is a toll-like receptor (TLR) 7 and 8 agonist used topically to treat external genital and peri-anal warts caused by human papilloma virus, actinic keratosis and super cial basal cell carcinomas and potential to treat many other skin disorders [18][19][20][21][22][23][24][25][26]. Through activation of its receptors, IMQ application, even on a short-term basis, triggers in ammatory skin reactions that closely resemble those seen in psoriasis [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%